IMPLEMENTATION OF INTEGRATED SERVICE POLICY FOR PORT SERVICES TO SUPPORT EMPOWERMENT SEA DEFENSE AREA - Lukman Hakim (Indonesian Naval Technology College STTAL, 2022)
PT Indonesian Port Regional III Tanjung Perak Surabaya carries out provision activities, port services, especially in loading and unloading activities for goods and containers with the right volume increase. This study aims to describe and interpret the implementation of the policy of implementing integrated port services, especially in loading and unloading activities at Port of Perak Surabaya, identifyingand investigating supporting factors and inhibiting the implementation of integrated services for stocking services, especially in loading and unloading activities at Port of Perak. Surabaya, as well as compiling the best integrated service policy models in the management of integrated port services, especially in sustainable loading and unloading activities to support the empowerment of the sea dimension defense area. The type of research used is descriptive qualitative, with the analysis of research on the implementation of grindle policies consisting of content of policy (policy content) and contex of implementation, where integrated services port services, especially in loading and unloading activities the existing one involves a lot of interests and management. Keywords: policy implementation, integrated service, loading and unloading, ports, empowerment of sea dimension defense areas.